PENGARUH KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PT. TELKOM INDONESIA SEMARANG - Nicko Achmad Pradityo; Rodhiyah Rodhiyah; Saryadi Saryadi (Universitas Diponegoro, 2013)
The research was conducted to determine the influence of leadership and organizational climate for the employee’s performance in PT Telkom Indonesia Tbk Semarang. This type of research is explanatory with the techniques of data collection through questionnaire. The sampling technique used proportional random sampling, the sample of 103 peoples who are the employee PT Telkom Indonesia Tbk Semarang. The method of analysis used in this study is Quantitative data analysis. The results of this study indicate that leadership have a positive and significant impact on employee performance in the amount of 37%.. Organizational climate is also positive and significant influence on employee performance . in the amount of 47,4%%. Leadership and organizational climate and significant positive effect on employee performance and organizational climate value significant positive effect on employee performance in the amount of 74,8%. The conclusion of this study is leadership, organizational climate on PT Telkom Indonesia Tbk Semarang is good. The test results showed that with the SPSS leadership and organizational climate have a significant impact on employee performance either simultaneously or partially.